Exploring the impacts of story telling activities on students’ English pronunciation learning strategies - Devi Ayu Wulandari; Andi Rustandi; Iskhak Said (Universitas Galuh, 2026)
Storytelling activities play an important role in improving students’ English pronunciation learning strategies, especially in the context of language acquisition. This study explores the impact of storytelling activities on students’ pronunciation as well as students’ responses to the use of storytelling activities to support their pronunciation in a high school in Ciamis using a qualitative case study approach. Data were collected through observations and interviews to gain a comprehensive insight into students’ experiences and perceptions of storytelling as a learning method. Findings showed that students generally showed a positive impact towards storytelling, highlighting its engaging nature and effectiveness in improving their pronunciation. Many students reported increased awareness of pronunciation nuances and greater confidence in speaking while participating in storytelling activities. However, challenges such as anxiety associated with complex vocabulary and pressure to perform in front of peers were also identified, which sometimes hindered their participation. This study emphasizes the importance of collaborative learning and peer interaction in fostering a supportive environment for language learning. Equally important is the verbal and non-verbal support and feedback from teachers that make students more enthusiastic in storytelling activities. This study suggests that educators use more diverse storytelling formats and provide targeted feedback to enhance the effectiveness of storytelling in improving pronunciation skills. In addition, the findings also indicate the need for strategies that can address students' anxiety and encourage a more relaxed learning atmosphere. Future research should investigate the long-term effects of storytelling on pronunciation and explore the integration of technology in storytelling activities to further engage students and enhance their learning experience.